Relevansi Aliran Esensialisme Rekonstruksionisme dalam Pendidikan Agama Kristen Masa Kini - Veren Veronika Manu; Merfin Bengkiuk; Milka Kabu; Keren Rohi Kana (PT. PENERBIT TIGA MUTIARA, 2026)
The dynamics of modern education, marked by rapid social, cultural, and moral changes, require Christian Religious Education (CRE) not only to preserve its faith-based foundations but also to respond critically and constructively to contemporary challenges. The main issue addressed in this study is how CRE can integrate the steadfastness of theological values with social sensitivity without losing its Christian identity. This study aims to analyze the relevance and contribution of the philosophical streams of Essentialism and Reconstructionism in the development of contemporary Christian Religious Education. The research employs a qualitative approach through a literature review, using descriptive–interpretative analysis of relevant scientific, philosophical, and theological sources. The findings indicate that Essentialism makes a significant contribution to strengthening the foundations of faith, shaping Christian character, and internalizing core Christian values that are normative and sustainable. Conversely, Reconstructionism positions CRE as a means of social renewal that encourages learners to actively engage in justice, social responsibility, and societal transformation. The integration of these two philosophical approaches enables CRE to develop holistically by balancing spiritual, moral, and social dimensions within the educational process. The conclusion of this study affirms that Essentialism and Reconstructionism possess strategic relevance as a philosophical foundation for contextual and transformative Christian Religious Education. The novelty of this research lies in its integrative philosophical model that harmonizes the firmness of faith with an orientation toward social change, thereby offering a new conceptual framework for the development of Christian Religious Education that is adaptive to the challenges of modern education without losing its theological essence.